Caracterización de suelos en la Quinta Experimental Punzara de la Universidad Nacional de Loja, para su posible uso como material de impermeabilización de reservorios - Nagua Medina, Renzo Rodrigo (2024)
In response to the need to guarantee the availability of water resources during low water levels, the study of soils is focused on the search for alternatives as waterproofing material in the construction of reservoirs. This is very relevant mainly for rural areas where there are reservoirs built in an empirical way, which fail mainly due to water infiltration. In this context, the objective of this work is to know the characteristics of the soils present in the Punzara Experimental Farm of the National University of Loja, identifying those that are suitable as waterproofing material. As a methodology, the first step was to go out and reconnoiter the study site, then, the placement of points to be sampled on a location map where 10 samples were established according to their characteristics found visually and followed by their sampling, then, the ASTM standards were analyzed in order to characterize the soils through the tests performed in the Construction Materials and Soils and Bromatology laboratories, then they were classified by the SUCS and AASHTO systems and finally they were compared based on previous research. The results show that the soils correspond to sands with silts and clays of high and low plasticity, with low volumetric change. Regarding permeability, it was found that the soils reach low hydraulic coefficients ranging from 1.81*10-6 to 9.3*10-8 cm/s when their density is increased by compaction, particularly samples P4, P7 and P9, which have a good behavior because the are minimally permeable.